The construction of Latina/o literary imaginaries : essays on alternative worldviews - Kabalen de Bichara, Donna M. (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2018)
This book explores the cultural and historical imaginary expressed in literary works that emphasize Latina/o world views. The essays here employ critical approaches based on discourse and cultural analyses that highlight individual and collective identity. They encompass a wide spectrum of topics that deal with border newspapers published early in the twentieth century and their function as a forum for conserving memory based on cultural values and religious beliefs; life writing and fictional rewritings of memory; autobiographical texts that emphasize the diasporic experience of immigrants; a.
The Hispanic periodical and promotion of moral and cultural values: La prensa -- Expressions of conflicting worldviews in religious print culture: Casa editorial revista católica and Casa bautista de publicaciones -- Unhailed heroines -- Performing autobiography and identity in The adventures of Don Chipote, or, when parrots breastfeed, by Daniel Venegas -- Narrating a clandestine existence: Ramón "Tianguis" Pérez's Diary of an undocumented immigrant -- Self and collective representation in the essays by Chicano authors Rolando Hinojosa and Sergio Troncoso -- Transcendental train yard and the creation of poetic and visual texts: the construction of cultural memory and identity.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: American literature -- Hispanic American authors -- History and criticism; Hispanic Americans in literature; Littérature américaine -- Auteurs américains d'origine latino-américaine -- Histoire et critique; Américains d'origine latino-américaine dans la littérature.; LITERARY CRITICISM -- American -- General; American literature -- Hispanic American authors; Hispanic Americans in literature; Criticism, interpretation, etc